Mid-infrared Semiconductor Optoelectronics - Krier, Anthony (Springer Series in Optical Sciences, 2006)
The practical realisation of optoelectronic devices operating in the 2-10 µm (mid-infrared) wavelength range offers potential applications in a variety of areas from environmental gas monitoring around oil rigs and landfill sites to the detection of pharmaceuticals, particularly narcotics. In addition, an atmospheric transmission window exists between 3 µm and 5 µm that enables free-space optical communications, thermal imaging applications and the development of infrared measures for "homeland security". Consequently, the mid-infrared is very attractive for the development of sensitive optical sensor instrumentation. Unfortunately, the nature of the likely applications dictates stringent requirements in terms of laser operation, miniaturisation and cost that are difficult to meet. Many of the necessary improvements are linked to a better ability to fabricate and to understand the optoelectronic properties of suitable high-quality epitaxial materials and device structures. Substantial progress in these matters is presented here. Mid-infrared Semiconductor Optoelectronics is an overview of the current status and technological development in this rapidly emerging area. It is composed of four parts. First, the basic physics and some of the main problems facing the design engineer (together with a comparison of possible solutions) are laid out. Next, there is a consideration of the multifarious lasers used as sources for mid-infrared technology, including an inspection of current approaches to the lack of such a source in the 3-4 µm region. Part III reviews recent work in light-emitting diodes and detectors and also deals with negative luminescence. The final part of the book is concerned with applications and highlights, once more, the diversity and technological importance of the mid-infrared spectral region. With a world-wide authorship of experts working in a number of different mid-infrared-related fields Mid-infrared Semiconductor Optoelectronics will be an invaluable reference for researchers and graduate students drawn from backgrounds in physics, electronic and electrical engineering and materials science. Its breadth and thoroughness also make it an excellent starting point for further research and investigation.